Effect of crop geometry and in situ soil moisture conservation practices on yield attributes and yield of upland rice (Oryza sativa L.) - Alekhya, Gunturi; Jayakrishnakumar, V (ORYZA-An International Journal of Rice, 2021)
Rice is the most widely grown crop in India. With the decreasing availability of water for irrigation, farmers are now switching towards water efficient production systems such as upland rice. Moisture stress at critical stagesis one of the major reasons for low productivity of upland rice. So, the present study was conducted at college of Agriculture, Vellayani, Thiruvananthapuram, Kerala Agricultural University, Kerala, India. The experiment was conducted in RBD with nine treatments including two crop geometries viz., normal planting (20 cm x 10 cm) and paired row planting (10 cm x 10 cm) with 40 cm between paired rows, three rows of cowpea are grown in between two paired rows and in situ soil moisture conservation practices viz., live mulching of cowpea, hydrogelapplication and coirpith compost application were compared and analysed statistically on yield parameters and yield. Results revealed that, the treatment T9 (Paired row planting with live mulching of cowpea, hydrogel and coir pith compost application) favorably influenced the yield characters and yield of upland rice through proper conservation of moisture and improved availability of nutrients. The treatment T9 recorded the highest grain and straw yields of 3825 and 7700 kg ha-1 respectively with a harvest index (0.48) and was significantlysuperior to other treatments. It also recorded the highest moisture content in the soil as well as the maximum uptake and availability of nutrients.